Experimental verification of an LiDAR based gust rejection system for a quadrotor UAV - Mendez, Arthur P.; Whidborne, James F.; Chen, Lejun (IEEE, 2022)
This paper assesses the use of a ground-based wind measuring LiDAR (Light Detection and Ranging) for remote sensing of incoming wind gusts at the landing site of an autonomous quadrotor. The experimental verification results show that the scalar measurements from the LiDAR were able to recreate the horizontal wind vector even with wind direction variation. Comparisons were conducted against conventional cup anemometers with wind vanes, and these show a good correlation. Upwind LiDAR measurements were used to predict the downstream wind using a transport model. This prediction compared with the downwind measurement shows a good correlation. This wind preview information from the LiDAR is then incorporated into a disturbance feedforward control scheme to increase the gust resilience of the vehicle. Simulation and experimental results demonstrate the system's efficacy.
Keywords: Laser radar; Fluid flow measurement; Correlation; Uncertainty; Wind speed; Sea measurements; Feedforward systems